2005
DOI: 10.1002/nml.100
|View full text |Cite
|
Sign up to set email alerts
|

How are employees of the nonprofit sector motivated? A research need

Abstract: This article reviews research on motivation of employees in theT HIS ARTICLE EXPLORES the necessity of nonprofit specifications in the existing motivation theories. Most motivation-related nonprofit research concentrates on existing and well-documented motivation theories stemming from the for-profit sector. Three basic themes have received most attention in this respect: the two-factor theory by Herzberg, Mausner, and Snyderman (1957), the job characteristics model by Hackman and Oldham (1980), and the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 46 publications
5
64
0
7
Order By: Relevance
“…This change in the level of motivation could be the drive behind the scores on the other indicators. Previous research has shown and suggested relationships between motivation and self-efficacy (Schepers et al 2005), job satisfaction (Davis and Wilson 2000) and occupational commitment (Sinclair et al 2006). Furthermore, starting their profession, teachers have a certain perspective on what teaching entails.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This change in the level of motivation could be the drive behind the scores on the other indicators. Previous research has shown and suggested relationships between motivation and self-efficacy (Schepers et al 2005), job satisfaction (Davis and Wilson 2000) and occupational commitment (Sinclair et al 2006). Furthermore, starting their profession, teachers have a certain perspective on what teaching entails.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There are many ways managers can use in order to encourage employee compliance with goals and objectives of the organization, this can be in terms of monitoring schemes and also incentives (Leete, 2000). Research has shown employees in voluntary organizations are more concerned meeting the needs of the public as opposed to extrinsic rewards displaying a very large commitment to the goals and objectives in which they work (Schepers et al, 2005). Whether this is the case in all Voluntary organizations is highly debatable and we will be looking at whether this is the case at ABC.…”
Section: Motivation In Voluntary Organizationsmentioning
confidence: 99%
“…Hence, continued research in different settings is warranted to determine what sustains teachers to be motivated and enhance the inputs for better student developments/outcomes [42], [43]. Therefore, a PhD research project was carried out to explore the stakeholders' perceptions of what motivates successful teachers to remain in the small and remote islands of the Maldives.…”
Section: Literature Reviewmentioning
confidence: 99%